Maternal Income during Pregnancy is Associated with Chronic Placental Inflammation at Birth - Keenan-Devlin, Lauren S.; Ernst, Linda M.; Ross, Kharah M.; Qadir, Sameen; Grobman, William A.; Holl, Jane L.; Crockett, Amy; Miller, Gregory E.; Borders, Ann E. B. (American Journal of Perinatology, 2017)
Objective This study aims to examine whether maternal household income is associated with histological evidence of chronic placental inflammation.Study Design A total of 152 participants completed surveys of household income and consented to placenta collection at delivery and postpartum chart review for birth outcomes. Placental inflammatory lesions were evaluated via histological examination of the membranes, basal plate, and villous parenchyma by a single, experienced pathologist. Associations between household income and the presence of inflammatory lesions were adjusted for known perinatal risk factors.Results Overall, 45% of participants reporting household income below $30,000/y had chronic placental inflammation, compared with 25% of participants reporting income above $100,000 annually (odds ratio [OR] = 4.23, 95% confidence interval [CI] = 1.25, 14.28; p = 0.02). Middle-income groups showed intermediate rates of chronic inflammatory lesions, at 40% for those reporting $30,000 and 50,000 (OR = 3.60, 95% CI = 1.05, 12.53; p = 0.04) and 38% for those reporting $50,000 to 100,000 (OR = 1.57, 95% CI = 0.60, 4.14; p = 0.36). Results remained significant after adjustment for maternal age, race, and marital status.Conclusion Chronic placental inflammation is associated with maternal household income. Greater occurrence of placental lesions in low-income mothers may arise from a systemic inflammatory response to social and physical environmental factors.
Keywords: chronic inflammation; chronic deciduitis; chronic villitis; income; placenta; pregnancy; stress